Vysetrení produkce intracelulárních cytokinů T lymfocyty pomocí průtokové cytometrie--metodické problémy - Marecková, H; Ravdan, A; Fucíková, T; Janatková, I (Epidemiologie, mikrobiologie, imunologie, 2002)
The method of assessment of intracellular proteins by means of flow cytometry makes it possible to evaluate the production of different cytokines by a clearly defined cell (sub-population type, state of cell activation). If the method should become a routine functional test, it must be standardized. This was the objective of our work when, based on data in the literature, we detected all controversial points and investigated them experimentally. Quite unequivocally we can recommend only sodium heparin as an anticoagulation agent when examining whole blood. The paper solves problems regarding the selection of mitogens where the marked effect of the use of mitogens on the result and necessity to compare results obtained under equal conditions was demonstrated. The authors tested also the possibility of preserving blood before processing and the selection of suitable combinations of surface signs and cytokines. When seeking the optimal time for cultivation it is necessary to make a compromise between the maximum possible production of cytokines (the kinetics of production of different cytokines is moreover different) and the accuracy of measurement because detection of the CD4 molecule after a prolonged period of stimulation deteriorates. As the optimum the authors recommend 4.5 hour cultivation with phorbol myristate acetate. The results proved a much greater capacity to retain newly formed cytokines in the cell if brefeldin A is used instead of monensine. The outcome of the work is a standard protocol for assessment of intracellular cytokines.
Keywords: cytokiny; T-lymfocyty; průtoková cytometrie; Humans; lidé; Flow Cytometry; T-Lymphocytes; Cytokines